Evaluation of zebrafish as a model to study the pathogenesis of the opportunistic pathogen Cronobacter turicensis - Fehr, Alexander (Emerg Microbes Infect, 2015)
Bacteria belonging to the genus Cronobacter spp. have been recognized as causative agents of life-threatening systemic infections, primarily in premature, low-birth weight and/or immune-compromised neonates. Knowledge remains scarce regarding the underlying molecular mechanisms of disease development. In this study, we evaluated the use of a zebrafish model to study the pathogenesis of Cronobacter turicensis LMG 23827(T), a clinical isolate responsible for two fatal sepsis cases in neonates. Here, the microinjection of approximately 50 colony forming units (CFUs) into the yolk sac resulted in the rapid multiplication of bacteria and dissemination into the blood stream at 24 h post infection (hpi), followed by the development of a severe bacteremia and larval death within 3 days. In contrast, the innate immune response of the embryos was sufficiently developed to control infection after the intravenous injection of up to 10(4) CFUs of bacteria. Infection studies using an isogenic mutant devoid of surviving and replicating in human macrophages (ΔfkpA) showed that this strain was highly attenuated in its ability to kill the larvae. In addition, the suitability of the zebrafish model system to study the effectiveness of antibiotics to treat Cronobacter infections in zebrafish embryos was examined. Our data indicate that the zebrafish model represents an excellent vertebrate model to study virulence-related aspects of this opportunistic pathogen in vivo.